2022
DOI: 10.3389/fpsyg.2022.1054137
|View full text |Cite
|
Sign up to set email alerts
|

Research on the state of blended learning among college students – A mixed-method approach

Abstract: In the wake of the COVID-19 pandemic in 2019, China’s education leaders began to focus on and promote blended learning. The process is still in its infancy in Chinese colleges and universities, and its development remains a problem to be solved. By combining technology acceptance and student participation, this article proposes an analysis model for assessing the factors influencing blended learning. A questionnaire was designed and distributed, and 796 valid responses were collected. The mean and variance wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This is because BT is a teaching innovation that was created to solve issues that often occur in full online learning. BT promotes a complex and more interesting teaching, namely applying a teaching system by combining online + offline sessions [50,51], so that this strategy can be a powerful way to increase engagement and independence in learning [37].Other research reported that studentathletes with a low mood state category has slowly experienced positive changes in mood after participating BT group [12]. Likewise, research conducted by Zhao & Song [52], explained that BT has the potential to evoke enormous positive emotions in student athletes, thus they could more involved actively in the PE learning process.…”
Section: Discussionmentioning
confidence: 99%
“…This is because BT is a teaching innovation that was created to solve issues that often occur in full online learning. BT promotes a complex and more interesting teaching, namely applying a teaching system by combining online + offline sessions [50,51], so that this strategy can be a powerful way to increase engagement and independence in learning [37].Other research reported that studentathletes with a low mood state category has slowly experienced positive changes in mood after participating BT group [12]. Likewise, research conducted by Zhao & Song [52], explained that BT has the potential to evoke enormous positive emotions in student athletes, thus they could more involved actively in the PE learning process.…”
Section: Discussionmentioning
confidence: 99%
“…With modern and intelligent education being strongly advocated and developed, neural network models based on deep learning are heavily used in classroom detection tasks. In the task of assessing the quality of teaching and learning of student, information about student postures [5,6,7] plays a very important role in assessing the quality of teaching and in teacher understanding of student learning status in the classroom [8]. In the classroom, a student state of learning is demonstrated through a variety of classroom behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a meta-analysis conducted on the effectiveness of blended learning reported mixed findings (Poirier et al, 2019). Also, studies on the effects of blended learning focus on mathematics (Setiawan et al, 2022) and basic statistics (Yusoff et al, 2017) for K-12 level (Liu & Wang, 2022;Topping et al, 2020;Fazal & Bryant, 2019), and college level (Deng et al, 2022), while the impact of blended learning in graduate students specifically in advanced statistics has not been much explored.…”
Section: A Introductionmentioning
confidence: 99%